Use of primary health care services prior to suicide in the Norwegian population 2006-2015 - Lars Johan Hauge; Kim Stene-Larsen; Tine Kristin Grimholt; Carine Øien-Ødegaard; Anne Reneflot (BMC, 2018)
Abstract Background Studies report high rates of contact with general practitioners (GPs) in primary care in the time leading up to suicide, particularly among individuals with a history of mental health contact. However, the near lack of studies including population representative controls have prevented investigations into how the contact patterns of suicide victims compares to those of the general population. Methods By linking data from two national registries, this study investigated primary health care use in suicide victims aged 15 years and older during the period from 2007 to 2015 (n = 4926). Their rates of contact one year and one month prior to suicide were compared to the average rates in the general Norwegian population during the period by estimating relative risks across sex and age. Contact patterns one month prior to suicide were also investigated according to prior mental health consultations in primary care. Results The findings revealed a stable trend in contact with GPs in primary care during the observation period, with 79.6% of male and 89.0% of female suicide victims having consulted their GP within a year of the suicide. Corresponding rates one month prior to the suicide were 34.8 and 46.4%, respectively. At both points in time and across all age groups, suicide victims were considerably more likely to consult their GP than were the general population. Suicide victims without prior mental health contact were only modestly more likely to consult their GP within a month of the suicide as compared to the general population, while both the general population and suicide victims with prior mental health consultations had rates of contact well above those without, evident for both sexes. Conclusions Contact with GPs in primary care prior to suicide is common in both sexes and across most age groups, in particular for victims with prior mental health consultations. Younger males show the overall lowest rates of contact, and increased alternative efforts to reach this group, in addition to larger population strategies, may pose the most prominent preventive measures.